The Role of Customer Satisfaction in Mediating the Effect of Service Quality and Trust on Customer Loyalty at LPD Tanjung Benoa - Hae, Mensen Mone; Telagawathi, Ni Luh Wayan Sayang; Widiastini, Ni Made Ary (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the role of customer satisfaction in mediating the influence of service quality and trust on customer loyalty at LPD Tanjung Benoa. The phenomenon of declining customer numbers and decreasing levels of customer satisfaction formed the basis for conducting this research. Customer loyalty is an important factor for the sustainability of financial institutions; therefore, service quality and trust need to be improved in order to create sustainable customer satisfaction. This study employed a quantitative approach with an explanatory research design. The population consisted of all loan and deposit customers of LPD Tanjung Benoa, totaling 1,242 customers. The sampling technique used was probability sampling with a simple random sampling method, resulting in a sample of 160 respondents. Data were collected through the distribution of questionnaires using a Likert scale. The data analysis technique used was Structural Equation Modeling based on Partial Least Square (PLS-SEM). The results showed that service quality has a positive and significant effect on customer loyalty, trust has a positive and significant effect on customer loyalty, and customer satisfaction has a positive and significant effect on customer loyalty. In addition, service quality and trust were also proven to have a positive and significant effect on customer satisfaction. Customer satisfaction was able to mediate the influence of service quality on customer loyalty and also mediate the influence of trust on customer loyalty at LPD Tanjung Benoa.